Injection molding products
By adding liquid crystal polyester and fibrous filler to the thermoplastic resin molding material, the fiber length and filler ratio are optimized, and the problem of insufficient collision resistance of thermoplastic resin molding materials in the prior art is solved, achieving higher mechanical properties and lightness Quantitative effect.
Patent Information
- Application Number
- CN202080053700.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-09
- Filing Date
- 2020-08-04
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-08-04
AI Technical Summary
It is difficult for the existing thermoplastic resin molding materials to achieve sufficient collision-resistant load strength in automotive frame-based components, suspension-based components and impact-absorbing components, resulting in insufficient mechanical properties of the molded body during the lightweight process.
The thermoplastic resin containing more than 10% polypropylene and liquid crystal polyester was used, and fibrous filler was used in injection molded products. The ratio of fiber length was less than 1 mm was less than 40%. The ashing test was shown by the ashing test. -The cross-plane area is at least 3.5 times that before ashing, and the fiber length and filler ratio are optimized to improve the strength of the collision load resistance.
It significantly improves the anti-collision load strength of the injection molded products, ensures safety and mechanical properties during impact, and meets the lightweight and strength needs of automotive parts.
Smart Images

Figure CN114206579B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an injection molded product.
[0002] This application claims priority based on Japanese Patent Application No. 2019-148156 filed in Japan on August 9, 2019, and the contents are incorporated herein by reference. Background Art
[0003] In recent years, in the field of transportation equipment including automobiles and airplanes, the weight reduction of parts is being pursued for the purpose of improving fuel efficiency. In order to reduce the weight of parts, research is being conducted on using resin materials instead of existing metal materials as the material of each part. For example, by using thermoplastic resins as molding materials for frame components, suspension components, impact absorbing components, etc. for automobiles, it is possible to obtain automobiles that are lighter than existing products.
[0004] However, there is a problem that the mechanical properties of a molded body obtained from a molding material containing the above-mentioned thermoplastic resin are lower than those of a molded body obtained from a metal material.
[0005] To solve such a problem, a method of mixing fibers as a filler into a thermoplastic resin in order to improve the strength of a molding material such as a thermoplastic resin composition has been proposed (for example, see Patent Document 1).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2005-298663. Summary of the invention
[0009] Problems to be solved by the invention
[0010] In the formation of molded bodies such as frame members, suspension members, and impact absorbing members for automobiles, which account for a large proportion of the vehicle body weight, further weight reduction is required.
[0011] As molded bodies become more lightweight, ensuring the strength of the molded bodies becomes a problem. For example, in a shock absorbing member for an automobile, strength to resist collision loads is required from the perspective of the safety of the interior of the vehicle during a collision.
[0012] However, in a molded body obtained from a conventional molding material containing a thermoplastic resin and fibers, it is not possible to obtain a molded body strength required to withstand a collision load.
[0013] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an injection molded product having improved strength particularly against collision loads.
[0014] Means for solving problems
[0015] In order to solve the above-mentioned problems, the present invention adopts the following configuration.
[0016] An injection molded article according to one embodiment of the present invention is an injection molded article containing a thermoplastic resin and a fibrous filler, characterized in that the thermoplastic resin contains at least one selected from the group consisting of polypropylene and liquid crystalline polyester in an amount of 10% by mass or more relative to the total amount of the thermoplastic resin; the proportion of the fibrous filler having a fiber length of less than 1 mm in the injection molded article is less than 40% by mass relative to the total amount of the fibrous filler; and through the following [ashing test], the longitudinal-transverse plane area of the test piece after ashing is 3.5 times or more relative to the longitudinal-transverse plane area of the test piece before ashing.
[0017] [Ashing test]
[0018] Step (1): Cut out a test piece of 10 mm in length and 10 mm in width from the injection molded product (the vertical-horizontal plane area of the test piece before ashing is 100 mm). 2 ).
[0019] Step (2): The test piece is subjected to a heat treatment (ashing) to completely remove the resin portion.
[0020] Step (3): Arrange the test piece after ashing so that the longitudinal-transverse plane of the test piece after ashing corresponds to the longitudinal-transverse plane of the test piece before ashing, and calculate the longitudinal-transverse plane area of the test piece after ashing by image analysis software.
[0021] In the injection molded article according to one aspect of the present invention, the ratio of the fibrous filler having a fiber length exceeding 5 mm in the injection molded article is preferably 30% by mass or more relative to the total amount of the fibrous filler.
[0022] In the injection-molded article according to one aspect of the present invention, the length-weighted average fiber length of the fibrous filler is preferably 4 mm or more.
[0023] The injection molded article according to one embodiment of the present invention preferably contains 40 to 70 parts by mass of the thermoplastic resin and 30 to 60 parts by mass of the fibrous filler.
[0024] In the injection-molded article according to one embodiment of the present invention, the fibrous filler is preferably glass fiber.
[0025] Effects of the Invention
[0026] According to one aspect of the present invention, it is possible to provide an injection molded product having improved strength particularly against collision loads. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1: is a figure which shows the test piece after the ashing test, is a photograph of the test piece after the ashing, and is a binary image of the test piece after the ashing.
[0028] Figure 2 Schematic diagram showing an example of a production apparatus for first particles. DETAILED DESCRIPTION
[0029] (Injection molding products)
[0030] The injection molded product of the present embodiment contains a thermoplastic resin and a fibrous filler.
[0031] In the injection molded product of the present embodiment, the ratio (mass ratio) of the thermoplastic resin to the fibrous filler is preferably 40 to 70 parts by mass of the thermoplastic resin and 30 to 60 parts by mass of the fibrous filler, more preferably 45 to 70 parts by mass of the thermoplastic resin and 30 to 55 parts by mass of the fibrous filler, further preferably 45 to 65 parts by mass of the thermoplastic resin and 35 to 55 parts by mass of the fibrous filler.
[0032] In the injection molded article, the ratio of the thermoplastic resin to 100 mass % of the injection molded article is preferably 40 to 70 mass %, more preferably 45 to 70 mass %, and even more preferably 45 to 65 mass %.
[0033] In the injection molded article, the ratio of the fibrous filler to 100 mass % of the injection molded article is preferably 30 to 60 mass %, more preferably 30 to 55 mass %, and even more preferably 35 to 55 mass %.
[0034] Preferably, the ratio of the thermoplastic resin is 40 to 70% by mass, and the ratio of the fibrous filler is 30 to 60% by mass, relative to 100% by mass of the injection molded product. More preferably, the ratio of the thermoplastic resin is 45 to 70% by mass, and the ratio of the fibrous filler is 30 to 55% by mass, relative to 100% by mass of the injection molded product. Further preferably, the ratio of the thermoplastic resin is 45 to 65% by mass, and the ratio of the fibrous filler is 35 to 55% by mass, relative to 100% by mass of the injection molded product.
[0035] As long as the ratio of the fibrous filler is above the lower limit of the preferred range, the effect of improving the strength of the injection molded product by the fibrous filler can be obtained. On the other hand, as long as it is below the upper limit of the preferred range, the fibrous filler is easily dispersed in the thermoplastic resin, and the fiber breakage due to collision between fibers during injection molding is not likely to occur.
[0036] The total content of the thermoplastic resin and the fibrous filler in the injection molded product of the present embodiment is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and may be 100% by mass, relative to the total amount of the injection molded product (100% by mass).
[0037] <Thermoplastic resin>
[0038] The injection molded product of the present embodiment contains at least one thermoplastic resin selected from the group consisting of polypropylene and liquid crystalline polyester (hereinafter referred to as “resin (Tr1)”).
[0039] Among the resins (Tr1), liquid crystalline polyester is preferably used because of its higher heat resistance and dimensional accuracy.
[0040] The liquid crystalline polyester contained in the injection molded article of the present embodiment is a polyester that exhibits liquid crystallinity in a molten state, and is preferably a polyester that melts under a temperature condition of 400° C. or less.
[0041] It should be noted that the liquid crystal polyester contained in the injection molded product of the present embodiment may be a liquid crystal polyester amide, a liquid crystal polyester ether, a liquid crystal polyester carbonate, or a liquid crystal polyester imide. The liquid crystal polyester contained in the injection molded product of the present embodiment is preferably a fully aromatic liquid crystal polyester formed by using only aromatic compounds as raw material monomers.
[0042] Typical examples of the liquid crystalline polyester contained in the injection molded product of the present embodiment include liquid crystalline polyesters formed by polymerization (polycondensation) of aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids and at least one compound selected from the group consisting of aromatic diols, aromatic hydroxylamines and aromatic diamines; liquid crystalline polyesters formed by polymerization of a plurality of aromatic hydroxycarboxylic acids; liquid crystalline polyesters formed by polymerization of aromatic dicarboxylic acids and at least one compound selected from the group consisting of aromatic diols, aromatic hydroxylamines and aromatic diamines; and liquid crystalline polyesters formed by polymerization of polyesters such as polyethylene terephthalate and aromatic hydroxycarboxylic acids.
[0043] Here, the aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic hydroxyamine and aromatic diamine may be replaced partially or entirely with their polymerizable derivatives, respectively, independently of one another.
[0044] Examples of polymerizable derivatives of compounds having a carboxyl group, such as aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids, include compounds (esters) obtained by converting a carboxyl group into an alkoxycarbonyl group or an aryloxycarbonyl group, compounds (acyl halides) obtained by converting a carboxyl group into a haloformyl group, and compounds (anhydrides) obtained by converting a carboxyl group into an acyloxycarbonyl group. Examples of polymerizable derivatives of compounds having a hydroxyl group, such as aromatic hydroxycarboxylic acids, aromatic diols, and aromatic hydroxylamines, include compounds (acylates) obtained by acylation of a hydroxyl group into an acyloxy group. Examples of polymerizable derivatives of compounds having an amino group, such as aromatic hydroxylamines and aromatic diamines, include compounds (acylates) obtained by acylation of an amino group into an acylamino group.
[0045] The liquid crystalline polyester contained in the injection molded product of the present embodiment preferably has a repeating unit represented by the following formula (1) (hereinafter, sometimes referred to as "repeating unit (1)"), and more preferably has a repeating unit (1), a repeating unit represented by the following formula (2) (hereinafter, sometimes referred to as "repeating unit (2)"), and a repeating unit represented by the following formula (3) (hereinafter, sometimes referred to as "repeating unit (3)").
[0046] (1)-O-Ar 1 -CO-
[0047] (2)-CO-Ar 2 -CO-
[0048] (3)-X-Ar 3 -Y-
[0049] (Ar 1 Ar represents phenylene, naphthylene or biphenylene. 2 and Ar 3 Each independently represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4). X and Y each independently represent an oxygen atom or an imino group (-NH-). 1 ,Ar 2 or Ar 3 The hydrogen atoms in the groups represented by may be independently substituted by halogen atoms, alkyl groups or aryl groups).
[0050] (4)-Ar 4 -Z-Ar 5 -
[0051] (Ar 4 and Ar 5 (wherein each independently represents a phenylene group or a naphthylene group. Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group).
[0052] Examples of the halogen atom include fluorine, chlorine, bromine and iodine atoms. Examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-hexyl, 2-ethylhexyl, n-octyl and n-decyl, and the number of carbon atoms thereof is preferably 1 to 10. Examples of the aryl group include phenyl, o-tolyl, m-tolyl, p-tolyl, 1-naphthyl and 2-naphthyl, and the number of carbon atoms thereof is preferably 6 to 20.
[0053] In the case where the hydrogen atoms are replaced by these groups, for each of Ar 1 ,Ar 2 or Ar 3 The number of the groups represented by is preferably 2 or less, and more preferably 1 or less, respectively and independently.
[0054] Examples of the alkylene group include a methylene group, an ethylene group, an isopropylene group, an n-butylene group, and a 2-ethylhexylene group, and the number of carbon atoms of the alkylene group is preferably 1 to 10.
[0055] The repeating unit (1) is a repeating unit derived from a predetermined aromatic hydroxycarboxylic acid. As the repeating unit (1), Ar 1 is a repeating unit of 1,4-phenylene (a repeating unit derived from p-hydroxybenzoic acid) and Ar 1 It is a repeating unit of 2,6-naphthylene (a repeating unit derived from 6-hydroxy-2-naphthoic acid).
[0056] It should be noted that the term “derived from” in the present specification means that in order to polymerize the raw material monomers, the chemical structure of the functional group that contributes to the polymerization is changed, and no other structural changes occur.
[0057] The repeating unit (2) is a repeating unit derived from a predetermined aromatic dicarboxylic acid. As the repeating unit (2), Ar 2 is a repeating unit of 1,4-phenylene (a repeating unit derived from terephthalic acid), Ar 2 is a repeating unit of 1,3-phenylene (a repeating unit derived from isophthalic acid), Ar 2 is a repeating unit of 2,6-naphthylene (derived from a repeating unit of 2,6-naphthalenedicarboxylic acid) and Ar 2 It is a repeating unit of diphenyl ether-4,4'-diyl (a repeating unit derived from diphenyl ether-4,4'-dicarboxylic acid).
[0058] The repeating unit (3) is a repeating unit derived from a predetermined aromatic diol, aromatic hydroxylamine or aromatic diamine. As the repeating unit (3), Ar 3 is a repeating unit of 1,4-phenylene (a repeating unit derived from hydroquinone, p-aminophenol or p-phenylenediamine) and Ar3 It is a repeating unit of 4,4'-biphenylene (a repeating unit derived from 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl).
[0059] The content of the repeating unit (1) is preferably 30 mol% or more, more preferably 30 mol% or more and 80 mol% or less, further preferably 40 mol% or more and 70 mol% or less, and particularly preferably 45 mol% or more and 65 mol% or less, relative to the total amount of all repeating units (the value obtained by dividing the mass of each repeating unit constituting the liquid crystalline polyester by the formula weight of each repeating unit to obtain the material equivalent (molar) of each repeating unit, and adding these values together).
[0060] The content of repeating unit (2) is preferably 35 mol% or less, more preferably 10 mol% or more and 35 mol% or less, further preferably 15 mol% or more and 30 mol% or less, and particularly preferably 17.5 mol% or more and 27.5 mol% or less, relative to the total amount of all repeating units.
[0061] The content of repeating unit (3) is preferably 35 mol% or less, more preferably 10 mol% or more and 35 mol% or less, further preferably 15 mol% or more and 30 mol% or less, and particularly preferably 17.5 mol% or more and 27.5 mol% or less, relative to the total amount of all repeating units.
[0062] As the content of the repeating unit (1) increases, the melt fluidity, heat resistance, strength and rigidity tend to be improved. However, when the content is too large, the melt temperature and melt viscosity tend to increase, and the temperature required for molding tends to increase.
[0063] The ratio of the content of repeating unit (2) to the content of repeating unit (3) is represented by [content of repeating unit (2)] / [content of repeating unit (3)] (mol / mol), and is preferably 0.9 / 1 to 1 / 0.9, more preferably 0.95 / 1 to 1 / 0.95, and further preferably 0.98 / 1 to 1 / 0.98.
[0064] It should be noted that the liquid crystalline polyester contained in the injection molded article of this embodiment may independently have two or more repeating units (1) to (3). In addition, the liquid crystalline polyester may have repeating units other than the repeating units (1) to (3), but the content thereof is preferably 10 mol% or less, more preferably 5 mol% or less relative to the total amount of all repeating units.
[0065] The liquid crystalline polyester contained in the injection molded article of the present embodiment preferably has, as repeating unit (3), a repeating unit in which X and Y are each an oxygen atom, i.e., a repeating unit derived from a predetermined aromatic diol, since the melt viscosity can be easily reduced. As repeating unit (3), it is more preferable to have only repeating units in which X and Y are each an oxygen atom.
[0066] The liquid crystalline polyester contained in the injection molded article of this embodiment is preferably produced by melt-polymerizing the raw material monomers corresponding to the repeating units constituting the liquid crystalline polyester and solid-phase polymerizing the obtained polymer (hereinafter sometimes referred to as "prepolymer"). Thus, a high molecular weight liquid crystalline polyester having high heat resistance or strength / rigidity can be produced with good operability.
[0067] Melt polymerization can be carried out in the presence of a catalyst. Examples of the catalyst include metal compounds such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, antimony trioxide, and nitrogen-containing heterocyclic compounds such as 4-(dimethylamino)pyridine and 1-methylimidazole. Preferably, nitrogen-containing heterocyclic compounds are used.
[0068] The flow start temperature of the liquid crystalline polyester contained in the injection molded article of the present embodiment is preferably 260° C. or higher, more preferably 260° C. or higher and 400° C. or lower, and further preferably 260° C. or higher and 380° C. or lower.
[0069] The higher the flow start temperature of the liquid crystalline polyester is, the more the heat resistance and strength of the liquid crystalline polyester tend to be improved. On the other hand, when the flow start temperature of the liquid crystalline polyester exceeds 400° C., the melting temperature or melt viscosity of the liquid crystalline polyester tends to increase. Therefore, there is a tendency for the temperature required for molding the liquid crystalline polyester to increase.
[0070] In this specification, the flow start temperature of the liquid crystalline polyester is also referred to as the viscosity temperature or the flow temperature, which is the temperature at which the molecular weight of the liquid crystalline polyester is estimated (see Naoyuki Koide, "Liquid Crystal Polymers - Synthesis, Molding, and Applications -", CMC Co., Ltd., June 5, 1987, p. 95).
[0071] The flow start temperature is determined by using a capillary rheometer to measure the liquid crystal polyester at 9.8 MPa (100 kg / cm 2 ) under a load of 4°C / min while melting and showing a viscosity of 4800 Pa·s (48000 poise) when extruded from a nozzle with an inner diameter of 1 mm and a length of 10 mm.
[0072] In the present embodiment, the liquid crystalline polyester may be used alone or in combination of two or more.
[0073] When two or more liquid crystalline polyesters are used in combination, as described later, liquid crystalline polyesters having different flow start temperatures are preferably used in combination.
[0074] In the thermoplastic resin contained in the injection molded product of the present embodiment, the proportion of the resin (Tr1) relative to the total amount of the thermoplastic resin (100 mass %) is 10 mass % or more, preferably 25 mass % or more, more preferably 50 mass % or more, further preferably 75 mass % or more, particularly preferably 90 mass % or more, and can be 100 mass %.
[0075] In the injection molded product of the present embodiment, the content of the resin (Tr1) is preferably 40 to 70 mass %, more preferably 45 to 65 mass %, and further preferably 45 to 60 mass % relative to the total amount (100 mass %) of the injection molded product.
[0076] The injection molded product of the present embodiment may contain, in addition to the resin (Tr1), a thermoplastic resin other than the resin (Tr1).
[0077] Examples of the thermoplastic resin other than the resin (Tr1) include polyamide, polyester other than liquid crystalline polyester, polysulfone, polyethersulfone, polyphenylene sulfide, polyether ketone, polyetheretherketone, polycarbonate, polyphenylene ether, and polyetherimide.
[0078] Among the thermoplastic resins contained in the injection molded product of the present embodiment, the ratio of the thermoplastic resins other than the resin (Tr1) is, for example, 0 to 25 mass %, or 0 to 10 mass % relative to the total amount (100 mass %) of the thermoplastic resins.
[0079] <Fiber-like filler>
[0080] The fibrous filler contained in the injection-molded article of the present embodiment may be a fibrous inorganic filler or a fibrous organic filler.
[0081] As fibrous inorganic fillers, glass fibers; carbon fibers such as PAN-based, asphalt-based, rayon-based, phenol-based, and lignin-based carbon fibers; ceramic fibers such as silica fibers, alumina fibers, and silica alumina fibers; metal fibers such as iron, gold, copper, aluminum, brass, and stainless steel; silicon carbide fibers and boron fibers. In addition, as fibrous inorganic fillers, whiskers such as potassium titanate whiskers, barium titanate whiskers, wollastonite whiskers, aluminum borate whiskers, silicon nitride whiskers, and silicon carbide whiskers can also be cited.
[0082] Examples of the fibrous organic filler include polyester fibers, para-aramid fibers or meta-aramid fibers, and PBO fibers.
[0083] Considering the wear load on the device during molding or availability, as the fibrous filler, at least one selected from the group consisting of carbon fibers such as PAN or asphalt and glass fibers is more preferred. In addition, for the purpose of imparting conductivity, a fibrous filler coated with a metal such as nickel, copper, or ytterbium can be used.
[0084] The tensile strength of the carbon fiber is preferably 2000 MPa or more, more preferably 3000 MPa or more, and further preferably 4000 MPa or more. In addition, the tensile ductility of the carbon fiber is preferably 0.5% or more, more preferably 1.0% or more, and further preferably 1.8% or more. By using high tensile strength and high ductility carbon fiber as a fibrous filler, fiber breakage in the processing process until the molded body is made can be suppressed, and the residual fiber can be longer, so that it becomes easy to obtain the effect of the invention.
[0085] Among them, PAN-based carbon fibers can be preferably used because they have a good balance among tensile strength, tensile elastic modulus, and tensile ductility and can retain a long residual fiber length.
[0086] It should be noted that the tensile strength, tensile elastic modulus, and tensile ductility of carbon fibers are values measured in accordance with JIS R7606:2000.
[0087] Examples of PAN-based carbon fibers include “TORAYCA (registered trademark)” manufactured by Toray Industries, Ltd., “Pyrofil (registered trademark)” manufactured by Mitsubishi Chemical Corporation, and “Tenax (registered trademark)” manufactured by Teijin Limited.
[0088] As pitch-based carbon fibers, for example, there can be mentioned “DIALEAD (registered trademark)” manufactured by Mitsubishi Chemical Corporation, “GRANOC (registered trademark)” manufactured by Nippon Graphite Fiber Co., Ltd., “DONACARBO (registered trademark)” manufactured by Osaka Gas Chemical Co., Ltd., and “KRECA (registered trademark)” manufactured by Kureha Corporation.
[0089] Examples of glass fibers include E glass (i.e., alkali-free glass), S glass or T glass (i.e., high-strength, high-elasticity glass), C glass (i.e., acid-resistant glass), D glass (i.e., low dielectric constant glass), ECR glass (i.e., an alternative glass to E glass that does not contain B2O3 or F2), and AR glass (i.e., alkali-resistant glass) for FRP reinforcing materials.
[0090] In the injection molded article of the present embodiment, glass fibers are preferably used as the fibrous filler from the viewpoints of strength to resist collision loads, balance of elastic modulus, and easy availability, and among them, E glass is particularly preferably used.
[0091] <Other ingredients>
[0092] The injection molded product of the present embodiment may contain one or more other fillers, additives, etc., in addition to the above-mentioned thermoplastic resin and fibrous filler, as necessary.
[0093] As other fillers, plate-like fillers, spherical fillers or other granular fillers may be used. Other fillers may be inorganic fillers or organic fillers.
[0094] Examples of the plate-like inorganic filler include talc, mica, graphite, wollastonite, glass flakes, barium sulfate, and calcium carbonate. The mica may be muscovite, phlogopite, fluorophlogopite, or tetrasilicon mica.
[0095] Examples of the particulate inorganic filler include silica, alumina, titanium oxide, glass beads, glass balloons, boron nitride, silicon carbide, and calcium carbonate.
[0096] Examples of additives include metering stabilizers, flame retardants, conductivity imparting agents, crystal nuclei, ultraviolet absorbers, antioxidants, vibration damping agents, antibacterial agents, insect repellents, deodorants, anti-coloring agents, heat stabilizers, mold release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foaming agents, viscosity modifiers, and surfactants.
[0097] <Dispersion state of fibrous fillers in injection molded products>
[0098] The length-weighted average fiber length of the fibrous filler in the injection-molded article of the present embodiment is preferably 4 mm or more, more preferably 4.5 mm or more, and even more preferably 5 mm or more.
[0099] On the other hand, the length-weighted average fiber length of the fibrous filler is preferably less than 50 mm, more preferably 40 mm or less, further preferably 20 mm or less, and particularly preferably 15 mm or less.
[0100] For example, the length-weighted average fiber length of the fibrous filler is preferably 4 mm or more and less than 50 mm, more preferably 4.5 mm or more and 40 mm or less, further preferably 5 mm or more and 20 mm or less, and particularly preferably 5 mm or more and 15 mm or less.
[0101] When the length-weighted average fiber length of the fibrous filler is greater than the lower limit of the preferred range, the strength against collision load is further increased. On the other hand, when it is less than the upper limit of the preferred range, molding becomes easier.
[0102] In the present embodiment, the fiber length and the length-weighted average fiber length of the fibrous filler in the injection-molded product are measured as follows.
[0103] Step (1): A test piece of 10 mm in width × 30 mm in length × 4 mm in thickness was cut out from the injection molded product and heated in a muffle furnace to remove the resin portion.
[0104] For example, when the fibrous filler is carbon fiber, the heating conditions are 500° C. for 3 hours, and when the fibrous filler is glass fiber, the heating conditions are 600° C. for 4 hours.
[0105] Step (2): The injection molded product from which the resin portion was removed was dispersed in 1000 mL of an aqueous solution to which 0.05% by volume of a surfactant (Micro90, manufactured by INTERNATIONAL PRODUCTS CORPORATION) was added to prepare a dispersion.
[0106] Step (3): Take 100 mL of the dispersion and dilute it 5 to 20 times with pure water. Take a portion of the diluted dispersion and observe the fibers using a microscope (VH-ZST (manufactured by KEYENCE) with a magnification of 20 times), and take 10 images for each sample in a manner that the imaged areas do not overlap.
[0107] However, when the fibrous filler is carbon fiber, 50 mL is taken out from the diluted dispersion, filtered under reduced pressure using a φ90 mm Kiriyama funnel with filter paper (No. 5C), and an image of the carbon fiber dispersed on the filter paper is photographed.
[0108] When the fibrous filler is glass fiber, 50 mL is taken out from the diluted dispersion liquid and dispersed in a petri dish, and then an image of the glass fiber dispersed in the petri dish is captured.
[0109] Step (4): Use the measuring tool of the microscope to measure the length of all fibers present in one captured image. It should be noted that the bent fibers are measured by multi-point measurement. The same operation is performed in the 10 captured images in sequence until the total number of measured fibers exceeds 500 to measure the fiber length. If the total number of fibers in the 10 captured images does not exceed 500, return to step (3), retake the image and measure the fiber length again based on the appropriately adjusted dilution ratio with pure water.
[0110] Step (5): From the fiber length of the fibrous filler measured in step (4), calculate the length-weighted average fiber length lm = (Σli 2 ×ni) / (Σli×ni), (Σni>500).
[0111] li: fiber length of fibrous filler.
[0112] ni: The number of fibrous fillers with fiber length li.
[0113] The proportion of the fibrous filler having a fiber length of less than 1 mm in the injection molded product of this embodiment, relative to the total amount (100 mass %) of the fibrous filler in the injection molded product, is 40 mass % or less, preferably 30 mass % or less, more preferably 25 mass % or less, and further preferably 20 mass % or less.
[0114] The smaller the proportion of the fibrous filler having a fiber length of 1 mm or less, the better. However, the lower limit thereof is, for example, 1% by mass or more or 2% by mass or more.
[0115] For example, the proportion of the fibrous filler having a fiber length of less than 1 mm is preferably from 1 mass % to 30 mass %, more preferably from 1 mass % to 25 mass %, further preferably from 1 mass % to 20 mass %, and particularly preferably from 2 mass % to 20 mass %.
[0116] When the proportion of the fibrous filler having a fiber length of 1 mm or less is within the preferred range, the development of cracks in the molded product is suppressed when an impact is applied to the molded product, and the strength against the collision load is more easily improved.
[0117] The proportion of the fibrous filler having a fiber length exceeding 5 mm in the injection molded product of this embodiment, relative to the total amount (100 mass %) of the fibrous filler in the injection molded product, is preferably 30 mass % or more, more preferably 35 mass % or more, further preferably 40 mass % or more, and particularly preferably 45 mass % or more.
[0118] The larger the proportion of the fibrous filler having a fiber length exceeding 5 mm, the more preferable it is. However, the upper limit thereof is, for example, 90% by mass or less or 80% by mass or less.
[0119] For example, the proportion of the fibrous filler having a fiber length exceeding 5 mm is preferably 30% by mass or more and 90% by mass or less, more preferably 35% by mass or more and 90% by mass or less, further preferably 40% by mass or more and 90% by mass or less, and particularly preferably 45% by mass or more and 80% by mass or less.
[0120] As long as the proportion of the fibrous filler having a fiber length exceeding 5 mm is within the preferred range, when an impact is applied to the molded product, energy can be efficiently consumed by extracting the fibrous filler from the matrix resin, and the strength against collision load can be more easily improved.
[0121] In the injection molded article of the present embodiment, according to the [Ashing Test] described below, the longitudinal-lateral plane area of the test piece after ashing is 3.5 times or more relative to the longitudinal-lateral plane area of the test piece before ashing.
[0122] [Ashing test]
[0123] Step (1): Cut out a test piece of 10 mm in length and 10 mm in width from the injection molded product (the vertical-horizontal plane area of the test piece before ashing is 100 mm). 2 ).
[0124] Step (2): The test piece is subjected to a heat treatment (ashing) to completely remove the resin portion.
[0125] Step (3): Arrange the test piece after ashing so that the longitudinal-transverse plane of the test piece after ashing corresponds to the longitudinal-transverse plane of the test piece before ashing, and calculate the longitudinal-transverse plane area of the test piece after ashing by image analysis software.
[0126] However, in the step (1), the thickness of the test piece before ashing is set to 5 mm or less. If the injection molded product has a portion with a thickness exceeding 5 mm, a portion with a length of 10 mm and a width of 10 mm is cut out and adjusted to a thickness of 5 mm or less and a difference between the maximum and minimum thicknesses of 0.5 mm or less by cutting or grinding.
[0127] The temperature of the heat treatment (ashing) in step (2) depends on the material forming the injection molded product, but is preferably 450 to 600°C in the case of a material containing polypropylene, and is preferably 500 to 600°C in the case of a material containing a liquid crystalline polyester.
[0128] As the image analysis software in step (3), image processing software (WinROOF2018, Mitani Shoji Co., Ltd.), image processing software (Luzex AP, Nireco Co., Ltd.), etc. can be used.
[0129] The longitudinal-lateral plane area of the test piece after ashing was obtained by binarizing the fiber portion and distinguishing the other portions using image analysis software (refer to Figure 1 ).
[0130] Figure 1 : is a figure which shows the test piece after the ashing test, is a photograph of the test piece after the ashing, and is a binary image of the test piece after the ashing.
[0131] (A) is the injection molded article of the present embodiment, and the test piece after ashing contains fiber bundles. On the other hand, (B) is the test piece after ashing contains almost no fiber bundles.
[0132] In the injection molded product of the present embodiment, the longitudinal-transverse plane area of the test piece after ashing is measured by the above-mentioned [Ashing Test] relative to the longitudinal-transverse plane area (100 mm 2 ) is 3.5 times or more, preferably 3.5 to 10 times, more preferably 4.0 to 10 times, and further preferably 5.0 to 10 times.
[0133] As long as the longitudinal-transverse plane area of the test piece after ashing is 3.5 times or more relative to the longitudinal-transverse plane area of the test piece before ashing, the strength against collision load can be particularly improved in injection molded products. On the other hand, as long as it is below the upper limit of the preferred range, the melt viscosity of the mixture of the thermoplastic resin and the fibrous filler can be suppressed from rising, thereby making the molding processability good.
[0134] As described above, the injection molded product of the present embodiment contains a thermoplastic resin and a fibrous filler. In addition, the injection molded product of the present embodiment includes at least one selected from the group consisting of polypropylene and liquid crystal polyester with a total amount of 10% by mass or more relative to the thermoplastic resin. That is, in the present embodiment, since polypropylene or liquid crystal polyester shows a moderate adhesion with the fibrous filler, when the injection molded product is impacted, the cracks in the injection molded product are not along the fracture direction of the fibrous filler, but are easily extended along the length direction of the fibrous filler (along the direction of the interface between the fibrous filler and the matrix resin). Thus, it is inferred that the result is that the fibrous filler is extracted from the matrix resin, and at this time, due to the effective energy consumption, the strength of the anti-collision load increases. In addition, the ratio of the fibrous filler with a fiber length of less than 1mm in the injection molded product of the present embodiment is less than 40% by mass relative to the total amount of the fibrous filler, and by the [ashing test], the longitudinal-transverse plane area of the test piece after ashing is more than 3.5 times the longitudinal-transverse plane area of the test piece before ashing. That is, in this embodiment, the fibrous filler is not excessively opened in the injection molded product, but is appropriately dispersed in the form of fiber bundles. In addition, by appropriately existing in the form of fiber bundles in the injection molded product, fiber breakage can be suppressed. Therefore, it is estimated that the injection molded product of this embodiment has improved strength against collision loads.
[0135] on the other hand, Figure 1 In the injection molded product in the state where the test piece after ashing contains almost no fiber bundles, the longitudinal-transverse plane area of the test piece after ashing is difficult to be more than 3.5 times the longitudinal-transverse plane area of the test piece before ashing due to the small number of fiber bundles. Since fiber breakage in the injection molded product is easy to occur, the strength required for impact absorbing components for automobiles is insufficient.
[0136] The injection molded article of the present invention has the following aspects.
[0137] [1] An injection molded article comprising a thermoplastic resin and a fibrous filler, wherein the thermoplastic resin contains 10% by mass or more of at least one selected from the group consisting of polypropylene and liquid crystalline polyester relative to the total amount of the thermoplastic resin, the proportion of the fibrous filler having a fiber length of 1 mm or less in the injection molded article is 40% by mass or less relative to the total amount of the fibrous filler, and the longitudinal-transverse plane area of the test piece after ashing is 3.5 times or more relative to the longitudinal-transverse plane area of the test piece before ashing as measured by the following [Ashing Test].
[0138] [Ashing test]
[0139] Step (1): Cut out a test piece of 10 mm in length and 10 mm in width from the injection molded product (the vertical-horizontal plane area of the test piece before ashing is 100 mm). 2 ).
[0140] Step (2): The test piece is subjected to a heat treatment (ashing) to completely remove the resin portion.
[0141] Step (3): Arrange the test piece after ashing so that the longitudinal-transverse plane of the test piece after ashing corresponds to the longitudinal-transverse plane of the test piece before ashing, and calculate the longitudinal-transverse plane area of the test piece after ashing by image analysis software.
[0142] [2] An injection molded article comprising a thermoplastic resin and a fibrous filler, wherein the thermoplastic resin comprises 50 to 100% by mass of at least one selected from the group consisting of polypropylene and liquid crystalline polyester relative to the total amount of the thermoplastic resin, the proportion of the fibrous filler having a fiber length of 1 mm or less in the injection molded article is 1% to 30% by mass relative to the total amount of the fibrous filler, and the longitudinal-transverse plane area of the test piece after ashing is 3.5 to 10 times the longitudinal-transverse plane area of the test piece before ashing as measured by the [ashing test].
[0143] [3] An injection molded article comprising a thermoplastic resin and a fibrous filler, wherein the thermoplastic resin comprises 75 to 100% by mass of at least one selected from the group consisting of polypropylene and liquid crystalline polyester relative to the total amount of the thermoplastic resin, the proportion of the fibrous filler having a fiber length of 1 mm or less in the injection molded article is 1% to 25% by mass relative to the total amount of the fibrous filler, and the longitudinal-transverse plane area of the test piece after ashing is 4.0 to 10 times the longitudinal-transverse plane area of the test piece before ashing as measured by the [ashing test].
[0144] [4] An injection molded article comprising a thermoplastic resin and a fibrous filler, wherein the thermoplastic resin comprises 90 to 100% by mass of at least one selected from the group consisting of polypropylene and liquid crystalline polyester relative to the total amount of the thermoplastic resin, the proportion of the fibrous filler having a fiber length of 1 mm or less in the injection molded article is 1% to 20% by mass relative to the total amount of the fibrous filler, and the area of the longitudinal-transverse plane of the test piece after ashing is 5.0 to 10 times the area of the longitudinal-transverse plane of the test piece before ashing as measured by the [ashing test].
[0145] [5] An injection molded product comprising a thermoplastic resin and a fibrous filler, wherein the thermoplastic resin is solely a liquid crystalline polyester, and the proportion of the fibrous filler having a fiber length of less than 1 mm in the injection molded product is 3.0 to 19.2% by mass relative to the total amount of the fibrous filler. According to the [ashing test], the longitudinal-transverse plane area of the test piece after ashing is 3.9 to 9.5 times the longitudinal-transverse plane area of the test piece before ashing.
[0146] [6] An injection molded article as described in any one of [1] to [5], wherein, through the [ashing test], the longitudinal-transverse plane area of the test piece after ashing is 3.5 to 10 times, preferably 4.0 to 10 times, more preferably 5.0 to 10 times, and even more preferably 3.9 to 9.5 times the longitudinal-transverse plane area of the test piece before ashing.
[0147] [7] An injection molded article as described in any one of [1] to [6], wherein the thermoplastic resin contains 50 to 100% by mass of at least one selected from the group consisting of polypropylene and liquid crystalline polyester, preferably 75 to 100% by mass, and more preferably 90 to 100% by mass, relative to the total amount of the thermoplastic resin.
[0148] [8] An injection molded article as described in any one of [1] to [7], wherein the thermoplastic resin contains 10% by mass or more of the liquid crystalline polyester relative to the total amount of the thermoplastic resin, preferably 50 to 100% by mass, more preferably 75 to 100% by mass, and even more preferably 90 to 100% by mass.
[0149] [9] An injection molded article as described in any one of [1] to [8], wherein the proportion of the fibrous filler having a fiber length of less than 1 mm in the injection molded article is 1% by mass or more and 30% by mass or less, preferably 1% by mass or more and 25% by mass or less, more preferably 1% by mass or more and 20% by mass or less, and further preferably 2% by mass or more and 20% by mass or less, relative to the total amount of the fibrous filler.
[0150]
[10] An injection molded article as described in any one of [1] to [9], wherein the proportion of the fibrous filler having a fiber length exceeding 5 mm in the injection molded article is 30% by mass or more relative to the total amount of the fibrous filler.
[0151]
[11] An injection molded article as described in
[10] , wherein the proportion of the fibrous filler having a fiber length exceeding 5 mm in the injection molded article is greater than 30% by mass and less than 90% by mass, preferably greater than 35% by mass and less than 90% by mass, more preferably greater than 40% by mass and less than 90% by mass, and further preferably greater than 45% by mass and less than 80% by mass, relative to the total amount of the fibrous filler.
[0152]
[12] The injection molded article according to any one of [1] to
[11] , wherein the length-weighted average fiber length of the fibrous filler is 4 mm or more.
[0153]
[13] An injection molded article as described in
[12] , wherein the length-weighted average fiber length of the fibrous filler is greater than or equal to 4 mm and less than or equal to 50 mm, preferably greater than or equal to 4.5 mm and less than or equal to 40 mm, more preferably greater than or equal to 5 mm and less than or equal to 20 mm, and even more preferably greater than or equal to 5 mm and less than or equal to 15 mm.
[0154]
[14] An injection molded article as described in any one of [1] to
[13] , which contains 40 to 70 parts by mass of the thermoplastic resin and 30 to 60 parts by mass of the fibrous filler, preferably contains 45 to 70 parts by mass of the thermoplastic resin and 30 to 55 parts by mass of the fibrous filler, and more preferably contains 45 to 65 parts by mass of the thermoplastic resin and 35 to 55 parts by mass of the fibrous filler.
[0155]
[15] An injection molded article as described in any one of [1] to
[14] , wherein the ratio of the thermoplastic resin is 40 to 70% by mass, and the ratio of the fibrous filler is 30 to 60% by mass, relative to 100% by mass of the injection molded article.
[0156]
[16] The injection molded article described in
[15] , wherein the ratio of the thermoplastic resin is 45 to 70% by mass, and the ratio of the fibrous filler is 30 to 55% by mass, relative to 100% by mass of the injection molded article.
[0157]
[17] The injection molded article as described in
[16] , wherein the ratio of the thermoplastic resin is 45 to 65% by mass, and the ratio of the fibrous filler is 35 to 55% by mass, relative to 100% by mass of the injection molded article.
[0158]
[18] An injection molded article as described in any one of [1] to
[17] , wherein the total content of the thermoplastic resin and the fibrous filler in the injection molded article is 80% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass, relative to the total amount of the injection molded article.
[0159]
[19] The injection molded article according to any one of [1] to
[18] , wherein the fibrous filler is glass fiber.
[0160] <Manufacturing method of injection molded products>
[0161] The injection molded product of the above-described embodiment can be produced by injection molding a thermoplastic resin composition (molding material) prepared by mixing a thermoplastic resin, a fibrous filler, and other components as necessary.
[0162] It should be noted that in this specification, a mixture obtained by mixing a thermoplastic resin and a fibrous filler is referred to as a "thermoplastic resin composition". In addition, a molding material for injection molding prepared by preparing the obtained mixture into pellets is also referred to as a "thermoplastic resin composition".
[0163] Hereinafter, an example of a method for producing the above-mentioned (injection molded product) will be described.
[0164] The method for manufacturing an injection molded product of the present embodiment is a method for manufacturing the above-mentioned (injection molded product), comprising: a process of impregnating first particles of a first thermoplastic resin with the fibrous filler, and mixing with second particles of a second thermoplastic resin that does not contain the fibrous filler and contains a second thermoplastic resin whose flow start temperature is lower than that of the first thermoplastic resin to obtain a particle mixture; and a process of injection molding the particle mixture.
[0165] [Step of Obtaining a Granular Mixture]
[0166] In the present embodiment, in the step of obtaining the particle mixture, the first particles and the second particles are mixed to obtain the particle mixture.
[0167] The first particles are composed of a resin structure in which the fibrous filler is impregnated with a first thermoplastic resin.
[0168] The first particles are obtained, for example, by impregnating a fibrous filler with a melt obtained by melt-kneading a first thermoplastic resin and other components as required, and pelletizing the fibrous filler to obtain particles in which the fibrous filler is fixed by the first thermoplastic resin.
[0169] The shape of the first particles may be cylindrical, disc-shaped, elliptical, elliptical, stone chess piece-shaped, spherical, or irregular, but is not limited thereto. From the viewpoint of productivity or handling during molding, cylindrical is more preferred.
[0170] Figure 2 One embodiment of the first particle production device is shown.
[0171] exist Figure 2 In the present embodiment shown, a case is described in which the pellets 15 made of the first thermoplastic resin composition are obtained by using the fiber roving 10 in which the fiber bundle 11 formed by a plurality of fibrous fillers being converged by a convergent is wound into a roll shape.
[0172] like Figure 2 As shown in FIG. 1 , the manufacturing apparatus 100 includes a preheating unit 121 , an impregnation unit 123 , a cooling unit 125 , a pulling unit 127 , a cutting unit 129 , and conveying rollers 101 to 109 . Figure 2 In the manufacturing apparatus 100 shown, the impregnation unit 123 is connected to the extruder 120 .
[0173] exist Figure 2 , a state where the fiber bundle 11 is continuously fed out from the fiber roving 10 is shown. In the present embodiment, pellets 15 made of the first thermoplastic resin composition are produced while the fiber bundle 11 fed out from the fiber roving 10 is fed in the longitudinal direction by feed rollers 101 to 109.
[0174] The fineness of the fiber roving 10 used in the production of the first pellet of the present embodiment is not particularly limited, but is preferably 200 g / 1000 m or more, more preferably 500 g / 1000 m or more, and further preferably 800 g / 1000 m or more. When the fineness of the fiber roving 10 is greater than the lower limit of the preferred range, the fiber roving 10 can be easily handled in the method for producing the first pellet.
[0175] In addition, the fineness of the fiber roving 10 is preferably 3750 g / 1000 m or less, more preferably 3200 g / 1000 m or less, and further preferably 2500 g / 1000 m or less. When the fineness of the fiber roving 10 is below the upper limit of the preferred range, the fibers are easily dispersed in the first thermoplastic resin. In addition, the fibers can be easily handled when the first pellets are produced.
[0176] That is, the fineness of the fiber roving 10 is preferably 200 g / 1000 m or more and 3750 g / 1000 m or less, and more preferably 800 g / 1000 m or more and 2500 g / 1000 m or less.
[0177] The number average fiber diameter of the fiber roving 10 is not particularly limited, but is preferably 1 to 40 μm, and more preferably 3 to 35 μm.
[0178] When the fibrous filler is carbon fiber, the number average fiber diameter of the fiber roving 10 is preferably 1 to 15 μm, more preferably 3 to 10 μm, and even more preferably 4 to 9 μm.
[0179] When the fibrous filler is glass fiber, the number average fiber diameter of the fiber roving 10 is preferably 5 to 35 μm, more preferably 10 to 25 μm, and even more preferably 10 to 20 μm.
[0180] The number average fiber diameter of the fiber roving 10 is a number average value obtained by observing the fibrous filler with a scanning electron microscope (1000 times) and measuring the fiber diameters of 500 randomly selected fibrous fillers.
[0181] When the number average fiber diameter of the fiber roving 10 is above the lower limit of the preferred range, the fibrous filler is easily dispersed in the first particle. In addition, the fibrous filler is easy to handle when the first particle is manufactured. On the other hand, when it is below the upper limit of the preferred range, the molded body is efficiently reinforced by the fibrous filler. Therefore, the injection molded product of the present embodiment can be given excellent Charpy impact strength.
[0182] In this embodiment, a fibrous filler treated with an astringent (sizing agent) is used. A fibrous filler treated with an appropriate sizing agent has better productivity and quality stability during pellet production and can reduce variation in physical properties of a molded product.
[0183] The astringent (sizing agent) is not particularly limited, and for example, nylon polymers, polyether polymers, epoxy polymers, ester polymers, urethane polymers, mixed polymers thereof, or modified polymers thereof can be cited. In addition, known coupling agents such as so-called silane coupling agents such as aminosilane and epoxysilane, and titanium coupling agents can be used.
[0184] In the fibrous filler used in the first particles of this embodiment, the single fibers do not necessarily need to be arranged in one direction. From the perspective of productivity in the process of manufacturing the molding material, it is preferred that the single fibers are arranged in one direction and the fiber bundles are continuous in the longitudinal direction of the fibers.
[0185] When the fibrous filler is glass fiber, the number of single yarns of the fiber roving 10 is preferably 1000 to 10000, more preferably 1000 to 8000, and even more preferably 1500 to 6000, from the viewpoint of improving economy and impregnation.
[0186] When the fibrous filler is carbon fiber, from the same viewpoint, the number of single yarns of the fiber roving 10 is preferably 10,000 to 100,000, more preferably 10,000 to 50,000, and even more preferably 10,000 to 30,000.
[0187] In the preheating section 121, the fiber bundle 11 fed from the fiber roving 10 is heated and dried. The heating temperature at this time is not particularly limited, and is, for example, 50 to 250°C.
[0188] In addition, the heating time in the preheating section 121 is not particularly limited, but is, for example, 3 to 30 seconds.
[0189] In the impregnation section 123 , the fiber bundle 11 is impregnated with the molding material M (the first thermoplastic resin and other components blended as needed) other than the fiber bundle 11 .
[0190] As described later, the first thermoplastic resin is preferably appropriately selected in consideration of the type of the second thermoplastic resin, melt viscosity, flow start temperature, etc. For example, preferred examples of the first thermoplastic resin include liquid crystalline polyesters and polypropylene.
[0191] The first thermoplastic resin may be used alone or in combination of two or more.
[0192] The fiber bundle 11 may be impregnated with a melt obtained by feeding the molding material M from the supply port 123 a and heating it in the impregnation section 123 , or the molding material M melt-kneaded by the extruder 120 may be fed from the supply port 123 a and impregnated with the fiber bundle 11 .
[0193] In addition, Figure 2 In the illustrated embodiment, the melt is impregnated into and coated on the fiber bundle 11 to obtain the resin structure 13 .
[0194] The heating temperature in the impregnation part 123 is appropriately determined according to the type of the first thermoplastic resin, and is preferably set to a temperature 10 to 80° C. higher than the flow start temperature of the first thermoplastic resin used, for example, 300 to 400° C.
[0195] In the impregnation section 123, it is preferred that 100 parts by mass of the first thermoplastic resin be impregnated with 90 to 250 parts by mass of the fibrous filler (fiber bundle 11), more preferably 100 to 240 parts by mass of the fibrous filler, and even more preferably 150 to 220 parts by mass of the fibrous filler, depending on the properties required for the molded article. As long as the amount of the fibrous filler is above the lower limit of the preferred range, the injection molded article is efficiently reinforced by the fibers. On the other hand, as long as it is below the upper limit of the preferred range, the fiber bundle is easily opened and the first thermoplastic resin is easily impregnated in the fiber bundle.
[0196] By changing the nozzle diameter of the die at the outlet of the impregnation section 123 according to the diameter of the fiber bundle 11 , the blending ratio of the first thermoplastic resin and the fibrous filler in the resin structure 13 can be adjusted.
[0197] In the cooling section 125, the heated resin structure 13 in the impregnation section 123 (the resin structure 13 in which the fiber bundle 11 is impregnated with the melt) is cooled, for example, to 50 to 150°C. The cooling time is not particularly limited, and is, for example, 3 to 30 seconds.
[0198] In the pulling section 127 , the resin structure 13 cooled in the cooling section 125 is continuously pulled and sent out to the next cutting section 129 .
[0199] In the cutting unit 129, the cooled resin structure 13 is cut into desired lengths to produce pellets 15. The cutting unit 129 includes, for example, a rotary blade or the like.
[0200] Using the above-described production apparatus 100 , as first particles of the present embodiment, particles in which a fibrous filler is fixed by a first thermoplastic resin are produced, for example, as follows.
[0201] A step of obtaining a resin structure.
[0202] While a fiber bundle 11 in which a plurality of single fibers are converged by a convergent is continuously fed out from the fiber roving 10 , the fiber bundle 11 is first heated and dried by the preheating unit 121 .
[0203] Next, while the dried fiber bundle 11 is supplied to the impregnation section 123, the molding material M melt-kneaded by the extruder 120 is introduced from the supply port 123a, and the molten molding material M is impregnated into the fiber bundle 11. Thus, the fiber bundle 11 is impregnated and coated with the melt to obtain the resin structure 13. Thereafter, the resin structure 13 in the heated state in the impregnation section 123 is cooled by the cooling section 125.
[0204] In the resin structure 13 obtained here, the fibers are arranged substantially in parallel along the longitudinal direction of the resin structure 13 .
[0205] “The fibers are arranged substantially parallel to the longitudinal direction of the resin structure” means that the angle between the longitudinal direction of the fibers and the longitudinal direction of the resin structure is substantially 0°, specifically, the angle between the longitudinal directions of the fibers and the resin structure is -5° to 5°.
[0206] The process of obtaining particles.
[0207] Next, the cooled resin structure 13 is pulled out into a strand shape by the pulling unit 127 and sent out to the cutting unit 129 .
[0208] Next, in the cutting unit 129 , the strand-shaped resin structure 13 is cut into predetermined lengths along its longitudinal direction to obtain pellets 15 .
[0209] The predetermined length of the pellet 15 mentioned here is the length of the pellet 15 set according to the required performance of the molded body made of the pellet 15. In the first pellet obtained by the production method of this embodiment, the length of the pellet 15 and the length of the fibers arranged in the pellet 15 are substantially the same.
[0210] The phrase “the length of the pellet is substantially the same as the length of the fibers” means that the length-weighted average fiber length of the fibers arranged in the pellet is 95 to 105% of the length in the longitudinal direction of the pellet.
[0211] As described above, the first particles (particles 15 ) in which the fibrous filler is impregnated with the first thermoplastic resin are produced.
[0212] The particles 15 are particles in which fibrous fillers are fixed by the first thermoplastic resin, and the fibrous fillers are arranged substantially in parallel along the length direction of the particles. In addition, the length of the fibrous fillers arranged in the particles 15 is substantially the same as the length of the particles. The length of the particles 15 manufactured in this embodiment depends on the required performance of the molded body made of the particles 15, and is, for example, 3 to 50 mm. The length of the particles refers to the length of the particles in the length direction.
[0213] In this way, since the fibrous filler is arranged roughly in parallel along the length direction of the particle, and the length of the fibrous filler is substantially the same as the length of the particle, when it is used as an injection molded product, the remaining fibrous filler in the injection molded product can be fiberized, thereby improving the heat resistance of the molded body and alleviating the anisotropy.
[0214] The arrangement direction of the fibrous filler in the particle can be confirmed by observing a cross section of the particle cut along the length direction with a microscope.
[0215] In the present embodiment, the fiber length and the length-weighted average fiber length of the fibrous filler in the pellets are measured in the following manner.
[0216] Step (1): 2 g of the pellets were heated in a muffle furnace to remove the resin portion (first thermoplastic resin).
[0217] For example, when the fibrous filler is carbon fiber, the heating conditions are 500° C. and 3 hours.
[0218] When the fibrous filler is glass fiber, the heating conditions are 600° C. and 4 hours.
[0219] Step (2): The particles from which the resin portion was removed were dispersed in 1000 mL of an aqueous solution to which 0.05% by volume of a surfactant (Micro90, manufactured by INTERNATIONAL PRODUCTS CORPORATION) was added to prepare a dispersion.
[0220] Step (3): 100 mL was taken out from the dispersion and diluted to 5 to 20 times with pure water. A portion of the diluted dispersion was taken out and the fibrous filler was observed using a microscope (VH-Z25, manufactured by KEYENCE, magnification 10 to 20 times), and 10 images were taken for each sample in a manner that the photographed areas did not overlap.
[0221] However, when the fibrous filler is carbon fiber, 50 mL is taken out from the diluted dispersion, filtered under reduced pressure using a φ90 mm Kiriyama funnel with filter paper (No. 5C), and an image of the carbon fiber dispersed on the filter paper is photographed.
[0222] When the fibrous filler is glass fiber, 50 mL is taken out from the diluted dispersion liquid and dispersed in a petri dish, and then an image of the glass fiber dispersed in the petri dish is captured.
[0223] Step (4): Use the microscope's measuring tool to measure the length of all fibers present in one captured image. It should be noted that bent fibers are measured by multi-point measurement, and fibers that are in contact with the edge of the image are not measured. The same operation is performed in sequence in the 10 captured images until the total number of measured fibers exceeds 500 to measure the fiber length. If the total number of fibers in the 10 captured images does not exceed 500, return to step (3), retake the image and measure the fiber length again based on appropriately adjusting the dilution ratio with pure water.
[0224] Step (5): From the fiber length of the fibrous filler measured in step (4), calculate the length-weighted average fiber length lm = (Σli 2 ×ni) / (Σli×ni), (Σni>500).
[0225] li: fiber length of fibrous filler.
[0226] ni: The number of fibrous fillers with fiber length li.
[0227] The second particles are composed of a resin structure that does not contain the fibrous filler and includes a second thermoplastic resin having a flow start temperature lower than that of the first thermoplastic resin.
[0228] The second pellets can be obtained, for example, by pelletizing a mixture of the second thermoplastic resin and, if necessary, other components by melt extrusion molding or melt compression molding.
[0229] The shape of the second particles may be cylindrical, disc-shaped, elliptical, elliptical, stone chess piece-shaped, spherical, or irregular, but is not limited thereto. From the viewpoint of productivity and handling during molding, cylindrical is more preferred.
[0230] In the method for producing an injection molded product according to the present embodiment, the second thermoplastic resin having a flow start temperature lower than that of the first thermoplastic resin is used.
[0231] The difference in flow start temperature between the second thermoplastic resin and the first thermoplastic resin is preferably 5° C. or more, more preferably 5 to 40° C. Alternatively, the difference in flow start temperature between the second thermoplastic resin and the first particles is preferably 5° C. or more, more preferably 5 to 40° C.
[0232] By selecting such a second thermoplastic resin relative to the first thermoplastic resin, the fibrous filler is appropriately dispersed in the injection molded product as a fiber bundle. In addition, since it exists as a fiber bundle during injection molding, fiber breakage is suppressed and the fibrous filler in the molded product remains for a long time, so it is easy to express the strength against collision loads.
[0233] The melt viscosity of the second thermoplastic resin under the melt kneading temperature conditions of the pellet mixture described below is preferably 5 to 500 Pa·s (measurement conditions: nozzle aperture 0.5 mm, shear rate 1000 s -1 ).
[0234] For example, the second thermoplastic resin includes liquid crystalline polyester, polypropylene, polyamide, polyester other than liquid crystalline polyester resin, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherketone, polyetheretherketone, polycarbonate, polyphenylene ether, polyetherimide, and the like.
[0235] The second thermoplastic resin may be used alone or in combination of two or more.
[0236] The above-mentioned first particles are mixed with the second particles to obtain a particle mixture.
[0237] In the case of an injection molded article, the first particles and the second particles are preferably mixed at a mixing ratio (mass ratio) of 40 to 70 parts by mass of the thermoplastic resin and 30 to 60 parts by mass of the fibrous filler.
[0238] For example, the mixing ratio (mass ratio) of the two is preferably 50 to 90 parts by mass of the first particles and 10 to 50 parts by mass of the second particles, more preferably 55 to 85 parts by mass of the first particles and 15 to 45 parts by mass of the second particles, and even more preferably 55 to 80 parts by mass of the first particles and 20 to 45 parts by mass of the second particles.
[0239] In the particle mixture, the mixing ratio of the first particles is preferably 50 to 90% by mass, more preferably 55 to 85% by mass, and even more preferably 55 to 80% by mass, relative to 100% by mass of the particle mixture.
[0240] In the particle mixture, the mixing ratio of the second particles is preferably 10 to 50% by mass, more preferably 15 to 45% by mass, and further preferably 20 to 45% by mass, relative to 100% by mass of the particle mixture.
[0241] The mixing ratio of the first particles is preferably 50 to 90% by mass and the mixing ratio of the second particles is preferably 10 to 50% by mass relative to 100% by mass of the particle mixture. The mixing ratio of the first particles is more preferably 55 to 85% by mass and the mixing ratio of the second particles is more preferably 15 to 45% by mass relative to 100% by mass of the particle mixture. The mixing ratio of the first particles is further preferably 55 to 80% by mass and the mixing ratio of the second particles is more preferably 20 to 45% by mass relative to 100% by mass of the particle mixture.
[0242] The first particles and the second particles may be separately put into a molding machine and mixed in the molding machine, or a mixture of the two particles may be prepared in advance. Alternatively, the first particles and the second particles may be particles in which the second particles are coated on the surface of the first particles.
[0243] [Step of injection molding the pellet mixture]
[0244] In the present embodiment, in the step of injection molding the pellet mixture, for example, the pellet mixture is melted using a known injection molding machine and the molten pellet mixture is injected into a mold for molding.
[0245] Examples of known injection molding machines include TR450EH3 manufactured by Sodick Co., Ltd. and hydraulic horizontal molding machine PS40E5ASE manufactured by Nissei Plastic Industries, Ltd.
[0246] The temperature conditions for injection molding are appropriately determined according to the type of thermoplastic resin, and the cylinder temperature of the injection molding machine is preferably set to a temperature 10 to 80° C. higher than the flow start temperature of the thermoplastic resin used.
[0247] For example, the melt-kneading temperature of the pellet mixture is preferably higher than the flow start temperature of the second thermoplastic resin and lower than the flow start temperature of the first thermoplastic resin or the first pellet.
[0248] Here, the melt-kneading temperature of the pellet mixture refers to the temperature at which the pellet mixture is melted or plasticized and kneaded, and specifically refers to the temperature of the plasticizing section of the injection molding machine at which the pellet mixture is melted and softened (melt-kneading temperature (plasticizing section)). More specifically, the melt-kneading temperature is preferably 260 to 340° C., more preferably 280 to 320° C., and further preferably 290 to 310° C. The metering section or plunger section is preferably 280 to 400° C., more preferably 290 to 380° C., and further preferably 300 to 370° C.
[0249] The temperature of the mold is preferably set within a range from room temperature (eg, 23° C.) to 180° C. from the viewpoint of the cooling rate of the thermoplastic resin and productivity.
[0250] As other injection conditions, the screw speed, back pressure, injection speed, holding pressure, holding time, etc. can be appropriately adjusted.
[0251] The method for manufacturing an injection molded product of the present embodiment described above comprises: a step of impregnating first particles of a first thermoplastic resin with the fibrous filler, mixing the particles with second particles that do not contain the fibrous filler and have a lower flow start temperature than the first thermoplastic resin, to obtain a particle mixture; and a step of injection molding the particle mixture.
[0252] In this embodiment, since a particle mixture of the first particle and the second particle is used, the fibrous filler is not excessively opened during the manufacture of the injection molded product, and is appropriately dispersed in the form of fiber bundles in the final manufactured injection molded product. In addition, by appropriately existing in the form of fiber bundles in the injection molded product, fiber breakage can be suppressed and the fibrous filler in the molded product remains for a long time (the fibrous filler with a fiber length of less than 1 mm is less, and the longitudinal-transverse plane area of the test piece after ashing is increased). Therefore, according to the manufacturing method of this embodiment, an injection molded product with improved strength against collision loads can be easily manufactured.
[0253] The method for producing an injection molded article of the present invention has the following aspects.
[0254]
[51] A method for producing an injection molded product according to any one of [1] to
[19] , comprising: mixing first particles containing a first thermoplastic resin impregnated with a fibrous filler with second particles containing a second thermoplastic resin having a lower flow start temperature than that of the first thermoplastic resin, to obtain a particle mixture; and
[0255] The process of injection molding the particle mixture.
[0256]
[52] The method for producing an injection molded product according to
[51] , wherein the difference in flow start temperature between the first thermoplastic resin and the second thermoplastic resin is 5° C. or more.
[0257]
[53] The method for producing an injection molded product according to
[51] or
[52] , wherein the difference in flow start temperature between the first pellet and the second thermoplastic resin is 5° C. or more.
[0258]
[54] A method for producing an injection molded product as described in any one of
[51] to
[53] , wherein the melt kneading temperature of the pellet mixture exceeds the flow start temperature of the second thermoplastic resin and is below the flow start temperature of the first thermoplastic resin.
[0259]
[55] A method for producing an injection molded product as described in any one of
[51] to
[54] , wherein the melt kneading temperature of the pellet mixture exceeds the flow start temperature of the second thermoplastic resin and is below the flow start temperature of the first pellet.
[0260] The injection molded article of the present embodiment described above can be used for any application to which thermoplastic resins can be generally used, and is particularly suitable for use in the automotive field.
[0261] As for the use in the automobile field, for example, as injection molded bodies for automobile interior decoration materials, there can be mentioned injection molded bodies for ceiling materials, injection molded bodies for wheel covers, injection molded bodies for trunk linings, injection molded bodies for instrument panel surface materials, injection molded bodies for handle covers, injection molded bodies for armrests, injection molded bodies for head pads, injection molded bodies for seat belt covers, injection molded bodies for shift lever covers, injection molded bodies for console boxes, injection molded bodies for horn pads, injection molded bodies for knobs, injection molded bodies for airbag covers, injection molded bodies for various decorative parts, injection molded bodies for various pillars, injection molded bodies for door lock bezels, injection molded bodies for glove boxes, injection molded bodies for defrost nozzles, injection molded bodies for scuff plates, injection molded bodies for steering wheels, injection molded bodies for steering column covers, etc.
[0262] In addition, as applications in the automotive field, for example, as injection-molded articles for automotive exterior materials, there are injection-molded articles for bumpers, injection-molded articles for air flow deflectors, injection-molded articles for fenders, injection-molded articles for side moldings, injection-molded articles for door mirror housings, injection-molded articles for floor guards, and the like.
[0263] Examples of other injection-molded articles for automobile parts include injection-molded articles for automobile headlights, injection-molded articles for glass runners, injection-molded articles for weather strips, injection-molded articles for drain hoses, injection-molded articles for window washer pipes, injection-molded articles for pipes, injection-molded articles for rack and pinion sleeves, injection-molded articles for gaskets, injection-molded articles for bumper beams, injection-molded articles for crash boxes, injection-molded articles for various components, injection-molded articles for suspension systems, injection-molded articles for front-end modules, injection-molded articles for radiator brackets, injection-molded articles for rear door interiors, and the like.
[0264] In addition, the injection molded product of this embodiment can be applied to sensors, LED lamps, connectors, sockets, resistors, relay boxes, switches, coil bobbins, capacitors, variable capacitor boxes, optical pickups, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, head mounts, energy modules, semiconductors, liquid crystal displays, FDD slides, FDD chassis, motor brush holders, parabolic antennas, computer-related parts, microwave oven parts, audio / sound equipment parts, lighting parts, air conditioning parts, office computer-related parts, telephone / FAX-related parts, and copier-related parts, in addition to the above.
[0265] [Example]
[0266] Hereinafter, the present invention will be described in further detail by way of specific examples, but the present invention is not limited to the following examples at all.
[0267] [Flow start temperature of thermoplastic resin]
[0268] Using a flow tester (Shimadzu Corporation "CFT-500" model), about 2 g of thermoplastic resin was filled into a cylinder of a mold equipped with a nozzle having an inner diameter of 1 mm and a length of 10 mm. Next, the flow tester was operated at 9.8 MPa (100 kg / cm 2 ) under a load of 4°C / min, while the temperature was raised at a rate of 4°C / min, the thermoplastic resin was melted and extruded from the nozzle, and the temperature (flow start temperature) when the viscosity of 4800 Pa·s (48000 poise) was measured and recorded as the flow start temperature of the thermoplastic resin. The measurement results are shown in Tables 2 and 3.
[0269] [Flow start temperature of the first particle]
[0270] The first particles were freeze-pulverized using a ball mill freeze-pulverizer ("JFC-1500" manufactured by Japan Analytical Industry Co., Ltd.) under predetermined conditions (amount of particles input: 5 g, pre-freezing time: 10 minutes, freeze-pulverization time: 10 minutes).
[0271] Next, the flow starting temperature of the first particles was measured in the same manner except that the thermoplastic resin in the above-mentioned [Flow starting temperature of thermoplastic resin] was changed to the first frozen-crushed particles.
[0272] <Manufacturing of preformed pellets>
[0273] Preformed pellets (1) to (5) are prepared by processing thermoplastic resins.
[0274] 《Manufacturing of prefabricated particles (1)》
[0275] Preformed particles (1) (LCP1 particles) were produced as follows.
[0276] In a reactor equipped with a stirrer, a torque meter, a nitrogen inlet pipe, a thermometer and a reflux cooler, 6-hydroxy-2-naphthoic acid (1034.99 g, 5.5 mol), 2,6-naphthalenedicarboxylic acid (378.33 g, 1.75 mol), terephthalic acid (83.07 g, 0.5 mol), hydroquinone (272.52 g, 2.475 mol, 0.225 mol excess relative to the total amount of 2,6-naphthalenedicarboxylic acid and terephthalic acid), acetic anhydride (1226.87 g, 12 mol) and 1-methylimidazole (0.17 g) as a catalyst were added, and after replacing the gas in the reactor with nitrogen, the temperature was raised from room temperature to 145° C. over 15 minutes under a nitrogen flow while stirring, and refluxed at 145° C. for 1 hour.
[0277] Next, the temperature was raised from 145° C. to 310° C. over 3.5 hours while distilling off by-produced acetic acid and unreacted acetic anhydride. After maintaining at 310° C. for 3 hours, the contents were taken out and cooled to room temperature.
[0278] The obtained solid material was crushed into a particle size of about 0.1 to 1 mm by a crusher, and then heated from room temperature to 250° C. in 1 hour, and from 250° C. to 295° C. in 8 hours, and maintained at 295° C. for 6 hours under a nitrogen atmosphere to perform solid phase polymerization. After solid phase polymerization, the mixture was cooled to obtain a powdery liquid crystal polyester.
[0279] In the liquid crystal polyester obtained here, the total amount of all repeating units is Ar 1 The repeating unit (1) is 55 mol% of 2,6-naphthylene, Ar 2 The repeating unit (2) is 17.5 mol% of 2,6-naphthylene, Ar 2 The repeating unit (2) is 5 mol% of 1,4-phenylene and Ar 3 The repeating unit (3) was 22.5 mol% of 1,4-phenylene and its flow starting temperature was 300°C.
[0280] Next, the obtained powdered liquid crystal polyester was pelletized using a twin-screw extruder (PMT47, manufactured by IKG) at a cylinder temperature of 300°C to produce pre-pellets (1) (LCP1 pellets). The flow start temperature of the produced LCP1 pellets was 294°C.
[0281] 《Manufacturing of prefabricated particles (2)》
[0282] Preformed particles (2) (LCP2 particles) were produced as follows.
[0283] In a reactor equipped with a stirrer, a torque meter, a nitrogen inlet pipe, a thermometer and a reflux cooler, 6-hydroxy-2-naphthoic acid (1034.99 g, 5.5 mol), 2,6-naphthalenedicarboxylic acid (378.33 g, 1.75 mol), terephthalic acid (83.07 g, 0.5 mol), hydroquinone (272.52 g, 2.475 mol, 0.225 mol excess relative to the total amount of 2,6-naphthalenedicarboxylic acid and terephthalic acid), acetic anhydride (1226.87 g, 12 mol) and 1-methylimidazole (0.17 g) as a catalyst were added, and after replacing the gas in the reactor with nitrogen, the temperature was raised from room temperature to 145° C. over 15 minutes under a nitrogen flow while stirring, and refluxed at 145° C. for 1 hour.
[0284] Next, the temperature was raised from 145° C. to 310° C. over 3.5 hours while distilling off by-produced acetic acid and unreacted acetic anhydride. After maintaining at 310° C. for 3 hours, the contents were taken out and cooled to room temperature.
[0285] The obtained solid material was crushed into a particle size of about 0.1 to 1 mm by a crusher, and then heated from room temperature to 250° C. for 1 hour, and from 250° C. to 310° C. for 10 hours, and maintained at 310° C. for 5 hours under a nitrogen atmosphere to perform solid phase polymerization. After solid phase polymerization, the mixture was cooled to obtain a powdery liquid crystal polyester.
[0286] In the liquid crystal polyester obtained here, the total amount of all repeating units is Ar 1 The repeating unit (1) is 55 mol% of 2,6-naphthylene, Ar 2 The repeating unit (2) is 17.5 mol% of 2,6-naphthylene, Ar 2 The repeating unit (2) is 5 mol% of 1,4-phenylene and Ar 3 The repeating unit (3) of 1,4-phenylene was 22.5 mol % and the flow starting temperature was 322°C.
[0287] Next, the obtained powdered liquid crystal polyester was pelletized using a twin-screw extruder (PMT47, manufactured by IKG) at a cylinder temperature of 320°C to produce pre-pellets (2) (LCP2 pellets). The flow start temperature of the produced LCP2 pellets was 303°C.
[0288] 《Manufacturing of prefabricated particles (3)》
[0289] Preformed particles (3) (LCP3 particles) were produced as follows.
[0290] In a reactor equipped with a stirring device, a torque measuring instrument, a nitrogen inlet pipe, a thermometer, and a reflux cooler, 994.5 g (7.2 mol) of p-hydroxybenzoic acid, 446.9 g (2.4 mol) of 4,4'-dihydroxybiphenyl, 299.0 g (1.8 mol) of terephthalic acid, 99.7 g (0.6 mol) of isophthalic acid, and 1347.6 g (13.2 mol) of acetic anhydride were added, and 0.2 g of 1-methylimidazole was added, and the inside of the reactor was fully replaced with nitrogen. Thereafter, the temperature was raised from room temperature to 150°C over 30 minutes under a nitrogen flow, and refluxed at 150°C for 1 hour.
[0291] Next, 0.9 g of 1-methylimidazole was added, and the temperature was raised from 150° C. to 320° C. over 2 hours and 50 minutes while distilling off by-produced acetic acid and unreacted acetic anhydride. The reaction was considered complete when the torque increased, and the contents were taken out and cooled to room temperature.
[0292] The obtained solid material was crushed into a particle size of about 0.1 to 1 mm by a crusher, and then heated from room temperature to 250° C. for 1 hour, and from 250° C. to 285° C. for 5 hours, and maintained at 285° C. for 3 hours under a nitrogen environment to perform solid phase polymerization. After solid phase polymerization, the mixture was cooled to obtain a powdery liquid crystal polyester. The flow start temperature of the obtained liquid crystal polyester was 327° C.
[0293] Next, the obtained powdered liquid crystal polyester was pelletized using a twin-screw extruder (PMT47, manufactured by IKG) at a cylinder temperature of 320°C to produce pre-pellets (3) (LCP3 pellets). The flow start temperature of the produced LCP3 pellets was 316°C.
[0294] 《Manufacturing of prefabricated particles (4)》
[0295] Preformed particles (4) (LCP4 particles) were produced as follows.
[0296] In a reactor equipped with a stirring device, a torque measuring instrument, a nitrogen inlet pipe, a thermometer, and a reflux cooler, 994.5 g (7.2 mol) of p-hydroxybenzoic acid, 446.9 g (2.4 mol) of 4,4'-dihydroxybiphenyl, 239.2 g (1.44 mol) of terephthalic acid, 159.5 g (0.96 mol) of isophthalic acid, and 1347.6 g (13.2 mol) of acetic anhydride were added, and 0.2 g of 1-methylimidazole was added, and the inside of the reactor was fully replaced with nitrogen. Thereafter, the temperature was raised from room temperature to 150°C over 30 minutes under a nitrogen flow, and refluxed at 150°C for 1 hour.
[0297] Next, 0.9 g of 1-methylimidazole was added, and the temperature was raised from 150° C. to 320° C. over 2 hours and 50 minutes while distilling off by-produced acetic acid and unreacted acetic anhydride. The reaction was considered complete when the torque increased, and the contents were taken out and cooled to room temperature.
[0298] The obtained solid material was crushed into a particle size of about 0.1 to 1 mm by a crusher, and then heated from room temperature to 220°C in 1 hour, and from 220°C to 240°C in 0.5 hours, and maintained at 240°C for 10 hours under a nitrogen environment to perform solid phase polymerization. After solid phase polymerization, the mixture was cooled to obtain a powdered liquid crystal polyester. The flow start temperature of the obtained liquid crystal polyester was 291°C.
[0299] Next, the obtained powdered liquid crystal polyester was pelletized using a twin-screw extruder (PMT47, manufactured by IKG) at a cylinder temperature of 290°C to produce pre-pellets (4) (LCP4 pellets). The flow start temperature of the produced LCP4 pellets was 284°C.
[0300] 《Manufacturing of prefabricated particles (5)》
[0301] Preformed particles (5) (LCP5 particles) were produced as follows.
[0302] A 3-liter four-necked separable flask equipped with a Dimroth condenser, a nitrogen inlet tube, a 1 / 4-shaped connecting tube equipped with a thermocouple for measuring the internal temperature, an anchor-type stirring blade, and a thermocouple also installed on the outside of the flask was used. 1207.3 g (8.74 mol) of 4-hydroxybenzoic acid, 608.4 g (3.23 mol) of 6-hydroxy-2-naphthoic acid, and 1345 g (13.2 mol) of acetic anhydride were added to the polymerization tank. Under a nitrogen flow, the external temperature of the flask was raised to 150° C. using a mantle heater, and an acetylation reaction was carried out under reflux for about 3 hours while stirring at 200 rpm. After the acetylation reaction, the temperature was raised at 1° C. / min and maintained at 310° C. to carry out melt polycondensation. During this period, acetic acid produced as a by-product in the polycondensation reaction was continuously distilled off. When the flow start temperature was measured 30 minutes after reaching 310° C. during the polymerization, it was 230° C. After reaching 230°C for 35 minutes, the stirring was stopped and the contents were taken out and cooled to room temperature. The obtained solid material was crushed to a particle size of about 0.1 to 1 mm with a pulverizer, and then heated from room temperature to 180°C in a nitrogen environment for 3 hours, and kept at 180°C for 2 hours, and then further heated to 270°C for about 7.5 hours, and kept at 270°C for 5 hours to perform solid phase polymerization. After solid phase polymerization, the liquid crystal polyester was cooled to obtain a powdered liquid crystal polyester. The flow start temperature of the liquid crystal polyester obtained here is 287°C.
[0303] Next, the obtained powdered liquid crystal polyester was pelletized using a twin-screw extruder (PMT47, manufactured by IKG) at a cylinder temperature of 280°C to produce pre-pellets (5) (LCP5 pellets). The flow start temperature of the produced LCP5 pellets was 262°C.
[0304] <Preparation of the first pellet>
[0305] First particles (1) to (10) in which a fibrous filler is impregnated with a thermoplastic resin are prepared.
[0306] Use with Figure 2 The same production apparatus as shown was used to produce first particles (1) to (10) as follows.
[0307] The extruder 120 used was a GTS-40 extruder (manufactured by Plastics Engineering Laboratory Co., Ltd.). The belt puller used was an EBD-1500A (manufactured by AIMEX Corporation). The following glass fibers were used as the fibrous filler.
[0308] Fibrous filler: Glass fiber roving manufactured by Nitto Bosho Co., Ltd. (HME-glass, fiber diameter 17 μm, fineness 1100 g / 1000 m)
[0309] Production of a first particle (1).
[0310] As preformed particles, preformed particles (3) (LCP3 particles) were used.
[0311] The resin structure 13 having 200 parts by mass of glass fiber bundles per 100 parts by mass of the preformed pellets (3) (LCP3 pellets) was produced specifically as follows.
[0312] A step of obtaining a resin structure.
[0313] The belt take-up machine (the take-up unit 127 ) was operated to continuously feed the glass fiber bundle 11 from the glass fiber roving 10 at a take-up speed of 10 m / min. First, the glass fiber bundle 11 was heated to 150° C. by the preheating unit 121 and dried.
[0314] Next, while supplying the dried glass fiber bundle 11 to the die (impregnation section 123) installed at the front end of the extruder 120, the molten pre-pellets (3) are introduced from the extruder 120 through the supply port 123a. The pre-pellets (3) are melted at 380°C in the die (impregnation section 123) and impregnated with the glass fiber bundle 11, and the bundle diameter is adjusted at the die (impregnation section 123) outlet with a die head having a nozzle diameter of 1.1 mm, so that a resin structure 13 having 200 parts by mass of glass fiber bundles relative to 100 parts by mass of the pre-pellets (3) is obtained.
[0315] In the resin structure 13 obtained here, the glass fibers are arranged substantially in parallel with the longitudinal direction of the first thermoplastic resin (LCP3) layer.
[0316] Thereafter, the resin structure 13 in a heated state in the mold (impregnation unit 123 ) is cooled to 150° C. or less in the cooling unit 125 .
[0317] The process of obtaining particles.
[0318] Next, the cooled resin structure 13 is pulled into a strand shape by the belt puller (pulling unit 127), sent to a granulator (cutting unit 129), and cut into a specified length along its length direction to obtain cylindrical (length 12 mm) pellets 15.
[0319] The pellet 15 was cut in the longitudinal direction, and the cross section obtained by cutting was observed under a microscope. As a result of this observation, it was confirmed that the arrangement direction of the glass fibers was substantially consistent with the longitudinal direction of the pellet and substantially parallel to the longitudinal direction of the pellet.
[0320] In addition, regarding the length of the glass fibers in the pellets, the length-weighted average fiber length was measured in the following procedure.
[0321] Step (1): 2 g of the pellets were heated in a muffle furnace at 600°C for 4 hours to remove the resin portion.
[0322] Step (2): The particles from which the resin portion was removed were dispersed in 1000 mL of an aqueous solution to which 0.05% by volume of a surfactant (Micro90, manufactured by INTERNATIONAL PRODUCTS CORPORATION) was added to prepare a dispersion.
[0323] Step (3): 100 mL was taken out from the dispersion and diluted to 10 times with pure water. 50 mL was taken out from the diluted dispersion and dispersed in a culture dish. The glass fibers dispersed in the culture dish were observed using a microscope (VH-Z25, manufactured by KEYENCE, magnification 10 times), and 10 images were taken for each sample in a manner that the shooting areas did not overlap.
[0324] Step (4): Use the microscope's measuring tool to measure the length of all fibers in one image. It should be noted that the bent fibers are measured by multi-point measurement, and the fibers that touch the edge of the image are not measured. The same operation is performed in 10 images taken in sequence until the total number of measured fibers exceeds 500 to measure the fiber length.
[0325] Step (5): From the fiber length of the glass fiber measured in step (4), calculate the length-weighted average fiber length lm = (Σli 2 ×ni) / (Σli×ni), (Σni>500).
[0326] li: fiber length of glass fiber.
[0327] ni: The number of glass fibers with fiber length li.
[0328] As a result, the length-weighted average fiber length of the glass fibers was the same as the particle length (12 mm).
[0329] Production of first particles (2).
[0330] As preformed particles, preformed particles (3) (LCP3 particles) were used.
[0331] A resin structure 13 having 192.3 parts by mass of glass fiber bundles based on 100 parts by mass of the preformed pellets (3) (LCP3 pellets) was obtained.
[0332] Except for this, a cylindrical (length 12 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0333] Production of the first particle (3).
[0334] Preformed particles (2) (LCP2 particles) were used as preformed particles, and the strand diameter was adjusted by a die having a nozzle diameter of 1.5 mm to obtain a resin structure 13 having 97.1 parts by mass of glass fiber bundles per 100 parts by mass of preformed particles (2) (LCP2 particles).
[0335] Except for this, a cylindrical (length 12 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0336] Production of first particles (4).
[0337] As preformed particles, preformed particles (2) (LCP2 particles) were used.
[0338] A resin structure 13 having 200 parts by mass of glass fiber bundles based on 100 parts by mass of the preformed pellets (2) (LCP2 pellets) was obtained.
[0339] Except for this, a cylindrical (length 12 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0340] Production of first particles (5).
[0341] As preformed particles, preformed particles (2) (LCP2 particles) were used.
[0342] A resin structure 13 having 200 parts by mass of glass fiber bundles based on 100 parts by mass of the preformed pellets (2) (LCP2 pellets) was obtained.
[0343] Except for this, a cylindrical (length 20 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0344] Production of first particles (6).
[0345] Preformed particles (2) (LCP2 particles) were used as preformed particles, and the strand diameter was adjusted by a die having a nozzle diameter of 1.5 mm to obtain a resin structure 13 having 95.2 parts by mass of glass fiber bundles per 100 parts by mass of preformed particles (2) (LCP2 particles).
[0346] Except for this, a cylindrical (length 12 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0347] Production of first particles (7).
[0348] Preformed particles (4) (LCP4 particles) were used as preformed particles, and the strand diameter was adjusted by a die head with a nozzle diameter of 2.0 mm to obtain a resin structure 13 having 58.7 parts by mass of glass fiber bundles per 100 parts by mass of preformed particles (4) (LCP4 particles).
[0349] Except for this, a cylindrical (length 12 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0350] Production of first particles (8).
[0351] Preformed particles (2) (LCP2 particles) were used as preformed particles, and the strand diameter was adjusted by a die having a nozzle diameter of 2.0 mm to obtain a resin structure 13 having 58.7 parts by mass of glass fiber bundles per 100 parts by mass of preformed particles (2) (LCP2 particles).
[0352] Except for this, a cylindrical (length 12 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0353] Production of first particles (9).
[0354] Preformed particles (1) (LCP1 particles) were used as preformed particles, and the strand diameter was adjusted by a die having a nozzle diameter of 2.0 mm to obtain a resin structure 13 having 58.7 parts by mass of glass fiber bundles per 100 parts by mass of preformed particles (1) (LCP1 particles).
[0355] Except for this, a cylindrical (length 12 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0356] Production of a first particle (10).
[0357] Preformed particles (5) (LCP5 particles) were used as preformed particles, and the strand diameter was adjusted by a die head with a nozzle diameter of 1.5 mm to obtain a resin structure 13 having 92.3 parts by mass of glass fiber bundles relative to 100 parts by mass of preformed particles (5) (LCP5 particles).
[0358] Except for this, a cylindrical (length 12 mm) pellet 15 was obtained in the same manner as the production of the first pellet (1) described above.
[0359] <Preparation of the second pellet>
[0360] Second particles (1) and (2) containing no fibrous filler and containing a thermoplastic resin are prepared.
[0361] As second particles (1) the prefabricated particles (4) (LCP4 particles) were used directly.
[0362] As second particles (2) the prefabricated particles (1) (LCP1 particles) were used directly.
[0363] Table 1 shows the composition and particle length of the first particles (1) to (10) and the composition of the second particles (1) to (2).
[0364] [Table 1]
[0365]
[0366] <Manufacturing of injection molded products>
[0367] The injection molded article of each example was produced through the steps of mixing the first pellets, the second pellets, and the metering stabilizer to obtain a pellet mixture, and injection molding the pellet mixture.
[0368] (Example 1)
[0369] The process of obtaining a particle mixture.
[0370] After the first granules (1) and the second granules (1) prepared above were mixed in the ratio described in Table 2, 0.04 parts by mass of CS-7 (calcium behenate, manufactured by Nitto Kasei Kogyo Co., Ltd.) as a metering stabilizer was added relative to 100 parts by mass of the mixture of the first granules (1) and the second granules (1), and the mixture was uniformly mixed to obtain a granule mixture.
[0371] The process of injection molding the pellet mixture.
[0372] The pellet mixture was put into the hopper of an injection molding machine TR450EH3 (manufactured by Sodick Co., Ltd.). The mixture was melt-kneaded in the injection molding machine at a temperature of 300°C in the plasticizing section (i.e., melt-kneading temperature), and injected into a mold at a mold temperature of 100°C at an injection speed of 20 mm / sec to form a multi-purpose test piece (A1 type) (thickness 4 mm) in accordance with JIS K7139. It should be noted that the gate was a film gate with a thickness of 4 mm from the upper edge of the gripping portion on one side of the multi-purpose test piece.
[0373] Other injection conditions: plunger temperature 360°C, screw speed (plasticizing part) 100 rpm, back pressure 0 MPa, holding pressure 100 MPa, holding time 5 seconds.
[0374] (Example 2)
[0375] A multi-purpose test piece (A1 type) (thickness 4 mm) in accordance with JIS K7139 was molded in the same manner as in Example 1 except that the first pellet (2) and the second pellet (1) were used in combination and the mixing ratio of the pellet mixture was changed.
[0376] (Example 3)
[0377] A multi-purpose test piece (A1 type) (thickness 4 mm) in accordance with JIS K7139 was molded in the same manner as in Example 1 except that the first pellet (3) and the second pellet (2) were used in combination and the mixing ratio of the pellet mixture was changed.
[0378] (Example 4)
[0379] A multi-purpose test piece (A1 type) (thickness 4 mm) in accordance with JIS K7139 was molded in the same manner as in the method for producing the injection molded article of Example 1 except that the first pellet (4) and the second pellet (2) were used in combination.
[0380] (Example 5)
[0381] A multi-purpose test piece (A1 type) (thickness 4 mm) in accordance with JIS K7139 was molded in the same manner as in the method for producing the injection molded article of Example 1 except that the first pellet (5) and the second pellet (2) were used in combination.
[0382] (Comparative Example 1)
[0383] A multi-purpose test piece (A1 type) (thickness 4 mm) in accordance with JIS K7139 was molded in the same manner as the method for producing the injection molded article of Example 1 except that the temperature of the plasticizing portion (ie, the melt kneading temperature) was changed.
[0384] (Comparative Example 2)
[0385] The multi-purpose test piece (A1 type) (thickness 4 mm) according to JIS K7139 was molded in the same manner as the injection molded product of Example 1, except that the first particle (6) and the second particle (2) were used in combination and the mixing ratio of the particle mixture was changed, and the temperature of the plasticizing section (i.e., the melt kneading temperature) was changed.
[0386] (Comparative Example 3)
[0387] A multi-purpose test piece (A1 type) (thickness 4 mm) in accordance with JIS K7139 was molded in the same manner as the method for producing the injection molded article of Example 3 except that the temperature of the plasticizing portion (ie, the melt kneading temperature) was changed.
[0388] (Comparative Example 4)
[0389] A multi-purpose test piece (A1 type) (thickness 4 mm) in accordance with JIS K7139 was molded in the same manner as the method for producing the injection molded article of Example 5 except that the temperature of the plasticizing section (ie, the melt kneading temperature) was changed.
[0390] (Comparative Example 5)
[0391] The multi-purpose test piece (A1 type) (thickness 4 mm) according to JIS K7139 was molded in the same manner as the injection molded product of Example 1, except that only the first particle (7) was added without the second particle and the temperature of the plasticizing section (i.e., the melt kneading temperature) was changed.
[0392] (Comparative Example 6)
[0393] The multi-purpose test piece (A1 type) (thickness 4 mm) according to JIS K7139 was molded in the same manner as the injection molded product of Example 1, except that only the first particle (8) was added without the second particle and the temperature of the plasticizing section (i.e., the melt kneading temperature) was changed.
[0394] (Comparative Example 7)
[0395] The multi-purpose test piece (A1 type) (thickness 4 mm) according to JIS K7139 was molded in the same manner as the injection molded product of Example 1, except that only the first particle (9) was added without the second particle and the temperature of the plasticizing section (i.e., the melt kneading temperature) was changed.
[0396] (Comparative Example 8)
[0397] The multi-purpose test piece (A1 type) (thickness 4 mm) according to JIS K7139 was molded in the same manner as the injection molded product of Example 1, except that only the first particle (10) was added without the second particle and the temperature of the plasticizing section (i.e., the melt kneading temperature) was changed.
[0398] For the injection molded products (multi-purpose test pieces (A1 type) (thickness 4 mm)) of each example, the length-weighted average fiber length of the fibrous filler in the injection molded products was measured, the proportion of the fibrous filler with a fiber length of 1 mm or less in the injection molded products was measured, the proportion of the fibrous filler with a fiber length of more than 5 mm in the injection molded products was measured, the ashing test was performed, and the expansion rate in the thickness direction of the test piece after ashing was measured. These measurement results are shown in Tables 2 and 3.
[0399] [Measurement of fiber length and length-weighted average fiber length of fibrous filler in injection molded products]
[0400] Step (1): A test piece of 10 mm in width × 30 mm in length × 4 mm in thickness was cut out from the center of a multi-purpose test piece (type A1) (thickness 4 mm), and heated in a muffle furnace at 600° C. for 4 hours to remove the resin portion.
[0401] Step (2): The substance from which the resin portion was removed from the test piece was dispersed in 1000 mL of an aqueous solution to which 0.05% by volume of a surfactant (Micro90, manufactured by INTERNATIONAL PRODUCTS CORPORATION) was added to prepare a dispersion.
[0402] Step (3): 100 mL was taken out from the dispersion and diluted to 10 times with pure water. 50 mL was taken out from the diluted dispersion and dispersed in a culture dish. Then, the glass fibers dispersed in the culture dish were observed using a microscope (VH-ZST (manufactured by KEYENCE) with a magnification of 20 times), and 10 images were taken for each sample in a manner that the shooting areas did not overlap.
[0403] Step (4): Use the measuring tool of the microscope to measure the length of all fibers present in one image. It should be noted that the bent fibers are measured by multi-point measurement. The same operation is performed in 10 images taken in sequence until the total number of measured fibers exceeds 500 to measure the fiber length.
[0404] Step (5): From the fiber length of the glass fiber measured in step (4), calculate the length-weighted average fiber length lm = (Σli 2 ×ni) / (Σli×ni), (Σni>500).
[0405] li: fiber length of glass fiber.
[0406] ni: The number of glass fibers with fiber length li.
[0407] [Measurement of the ratio of fibrous filler having a fiber length of 1 mm or less in injection molded products]
[0408] The value obtained by dividing the total fiber length of fibers having a fiber length of 1 mm or less measured in the above step (4) by the total fiber length of the fibers is taken as the ratio of the fibrous filler having a fiber length of 1 mm or less to the total amount of the fibrous filler in the injection molded product.
[0409] [Determination of the ratio of fibrous filler having a fiber length exceeding 5 mm in injection molded products]
[0410] The value obtained by dividing the total fiber length of fibers having a fiber length exceeding 5 mm measured in the above step (4) by the total fiber length of the fibers is taken as the ratio of the fibrous filler having a fiber length exceeding 5 mm to the total amount of the fibrous filler in the injection molded product.
[0411] [Ashing test]
[0412] Step (1): Cut out a rectangular test piece of 10 mm in length × 10 mm in width × 4 mm in thickness from the injection molded product (multi-purpose test piece (A1 type) (thickness 4 mm)) (the vertical-horizontal plane area of the test piece before ashing is 100 mm 2 ).
[0413] Step (2): The test piece is subjected to a heat treatment (ashing) at 600° C. to completely remove the resin portion.
[0414] Step (3): The test piece after ashing is arranged in such a way that the longitudinal-transverse plane of the test piece after ashing corresponds to the longitudinal-transverse plane of the test piece before ashing, and the longitudinal-transverse plane area of the test piece after ashing is calculated by image analysis software. The image analysis software uses image processing software (WinROOF2018, Mitani Shoji Co., Ltd.). The binarization condition is a binarization instruction with two thresholds, and the threshold is set to identify the outline of the test piece after ashing. In addition, in the case where an object other than the test piece such as the scale display in the image is mistakenly identified as an outline, the object mistakenly identified as the outline is deleted after binarization.
[0415] The longitudinal-transverse plane area of the test piece after ashing is divided by the longitudinal-transverse plane area of the test piece before ashing 100mm 2 , in order to calculate the area ratio after ashing to before ashing [after ashing / before ashing].
[0416] [Measurement of Expansion Ratio in Thickness Direction of Test Specimen after Ashing]
[0417] The expansion rate in the thickness direction of the test piece after ashing was calculated by the following formula.
[0418] Expansion rate of the test piece in the thickness direction after ashing = thickness of the thickest part of the test piece after ashing / thickness of the test piece before ashing
[0419] <Evaluation of injection molded products>
[0420] The injection molded product of each example was subjected to the following Charpy impact test to measure the Charpy impact strength and evaluate the strength against the collision load. The measurement results are shown in Tables 2 and 3.
[0421] Charpy impact test.
[0422] A non-notched test piece of 10 mm in width×80 mm in length×4 mm in thickness was cut out from the injection molded product (multi-purpose test piece (A1 type) (4 mm in thickness)) of each example.
[0423] The unnotched test piece was notched with a 45° V-groove (notch tip radius: 0.25 mm±0.05 mm) with a depth of 2 mm in accordance with ISO 2818 and JIS K7144. The notching tool (Toyo Seiki Co., Ltd., Model A-4) was used for the notching.
[0424] A notched test piece (notched test piece) was used to perform a Charpy impact test in accordance with ISO179-1 and JIS K7111-1 using pendulums of 2.0 J, 4.0 J, and 7.5 J. The Charpy impact strength of the notched test piece was the average value of five measurements.
[0425] [Table 2]
[0426]
[0427] [Table 3]
[0428]
[0429] The test piece after the ashing test is shown in Figure 1 middle, Figure 1 (A) is the injection molded product of Example 1, Figure 1 (B) is the injection molded product of Comparative Example 3.
[0430] Figure 1 (A): The injection molded product of Example 1, the test piece after ashing is in a state of containing fiber bundles. Through the above [Ashing Test], the longitudinal-transverse plane area of the test piece after ashing is relative to the longitudinal-transverse plane area of the test piece before ashing (100mm 2 ) is 3.9 times.
[0431] Figure 1 (B): The injection molded product of Comparative Example 3, the test piece after ashing is in a state where the fiber bundle is almost not included. Through the above [Ashing Test], the longitudinal-transverse plane area of the test piece after ashing is relative to the longitudinal-transverse plane area of the test piece before ashing (100mm 2 ) is 2.4 times.
[0432] From the results shown in Tables 2 and 3, it can be confirmed that the injection molded articles of Examples 1 to 5 to which the present invention is applied have higher Charpy impact strength values and further improved strength against collision loads than the injection molded articles of Comparative Examples 1 to 8.
[0433] It should be noted that, from the results shown in Tables 2 and 3, it can be confirmed that the effect of improving strength brought about by the application of the present invention is that the influence of the expansion coefficient in the thickness direction of the test piece after ashing is small, and the proportion of fibrous fillers with a fiber length of less than 1 mm and the specific area ratio before and after ashing contribute greatly.
[0434] Description of Reference Numerals
[0435] 100: manufacturing device, 101 to 109: conveying rollers, 120: extruder, 121: preheating unit, 123: impregnation unit, 125: cooling unit, 127: pulling unit, 129: cutting unit.
Claims
1. An injection molded product comprising a thermoplastic resin and a fibrous filler, wherein: The thermoplastic resin is a liquid crystalline polyester, The ratio of the fibrous filler having a fiber length of 1 mm or less in the injection molded product is 2% by mass or more and 40% by mass or less relative to the total amount of the fibrous filler. According to the following ashing test, the longitudinal-transverse plane area of the test piece after ashing is 3.5 times or more relative to the longitudinal-transverse plane area of the test piece before ashing, With respect to 100 mass % of the injection molded product, the ratio of the thermoplastic resin is 45 to 65 mass %, and the ratio of the fibrous filler is 35 to 55 mass %, The ratio of the fibrous filler having a fiber length exceeding 5 mm in the injection molded article is 45% by mass or more and 80% by mass or less relative to the total amount of the fibrous filler. The length-weighted average fiber length of the fibrous filler is 5.0 mm or more and 15 mm or less, Ashing test: Step 1: Cut out a test piece of 10 mm in length and 10 mm in width from the injection molded product. The vertical-horizontal plane area of the test piece before ashing is 100 mm. 2 ; Step 2, subjecting the test piece to a heat treatment, i.e., ashing, to completely remove the resin portion; as well as Step 3: The test piece after ashing is arranged so that the longitudinal-transverse plane of the test piece after ashing corresponds to the longitudinal-transverse plane of the test piece before ashing, and the area of the longitudinal-transverse plane of the test piece after ashing is obtained by image analysis software.
2. The injection molded article according to claim 1, wherein The total content of the thermoplastic resin and the fibrous filler is 90% by mass or more relative to 100% by mass of the total amount of the injection molded product.
3. The injection molded article according to claim 1 or 2, wherein: The fibrous filler is glass fiber.
